JNK-Dependent cJun Phosphorylation Mitigates TGFβ- and EGF-Induced Pre-Malignant Breast Cancer Cell Invasion by Suppressing AP-1-Mediated Transcriptional Responses - Anders Sundqvist; Oleksandr Voytyuk; Mohamed Hamdi; Herman E. Popeijus; Corina Bijlsma- van der Burgt; Josephine Janssen; John W.M. Martens; Aristidis Moustakas; Carl-Henrik Heldin; Peter ten Dijke; Hans van Dam (Cells, 2019)
Transforming growth factor-β (TGFβ) has both tumor-suppressive and tumor-promoting effects in breast cancer. These functions are partly mediated through Smads, intracellular transcriptional effectors of TGFβ. Smads form complexes with other DNA-binding transcription factors to elicit cell-type-dependent responses. Previously, we found that the collagen invasion and migration of pre-malignant breast cancer cells in response to TGFβ and epidermal growth factor (EGF) critically depend on multiple Jun and Fos components of the activator protein (AP)-1 transcription factor complex. Here we report that the same process is negatively regulated by Jun N-terminal kinase (JNK)-dependent cJun phosphorylation. This was demonstrated by analysis of phospho-deficient, phospho-mimicking, and dimer-specific cJun mutants, and experiments employing a mutant version of the phosphatase MKP1 that specifically inhibits JNK. Hyper-phosphorylation of cJun by JNK strongly inhibited its ability to induce several Jun/Fos-regulated genes and to promote migration and invasion. These results show that MEK-AP-1 and JNK-phospho-cJun exhibit distinct pro- and anti-invasive functions, respectively, through differential regulation of Smad- and AP-1-dependent TGFβ target genes. Our findings are of importance for personalized cancer therapy, such as for patients suffering from specific types of breast tumors with activated EGF receptor-Ras or inactivated JNK pathways.